Selective Ah Receptor Ligands Mediate Enhanced SREBP1 Proteolysis to Restrict Lipogenesis in Sebocytes. (21st June 2019) - Muku, Gulsum E; Blazanin, Nicholas; Dong, Fangcong; Smith, Philip B; Thiboutot, Diane; Gowda, Krishne; Amin, Shantu; Murray, Iain A; Perdew, Gary H
Abstract: The aryl hydrocarbon receptor (AHR) mediates 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD)-induced toxicity that can lead to chloracne in humans. A characteristic of chloracne, in contrast to acne vulgaris, is shrinkage or loss of sebaceous glands. Acne vulgaris, on the other hand, is often accompanied by excessive sebum production. Here, we examined the role of AHR in lipid synthesis in human sebocytes using distinct classes of AHR ligands. Modulation of AHR activity attenuated the expression of lipogenic genes and key proinflammatory markers in the absence of canonical DRE-driven transcription of the AHR target gene CYP1A1 . Furthermore, topical treatment with TCDD, which mediates DRE-dependent activity, and SGA360, which fails to induce DRE-mediated responses, both exhibited a decrease in the size of sebaceous glands and the number of sebocytes within each gland in the skin. To elucidate the mechanism of AHR-mediated repression of lipid synthesis, we demonstrated that selective AHR modulators, SGA360 and SGA315 increased the protein turnover of the mature sterol regulatory element-binding protein (mSREBP-1), the principal transcriptional regulator of the fatty acid synthesis pathway. Interestingly, selective AHR ligand treatment significantly activated the AMPK-dependent kinase (AMPK) in sebocytes. Moreover, we demonstrated an inverse correlation between the active AMPK and the mSREBP-1 protein, which is consistent with the previously reported role of AMPK in inhibiting cleavage of SREBP-1. Overall, our findings indicate a DRE-independent function of selective AHR ligands in modulating lipid synthesis in human sebocytes, which might raise the possibility of using AHR as a therapeutic target for treatment of acne.